Rytų aukštaičių uteniškių inesyvo ir iliatyvo priegaidės: audicinis tyrimas - Bacevičiūtė, Rima; Rinkauskienė, Regina (Baltistica, 2008)
THE SYLLABLE ACCENTS OF THE INESSIVE AND ILLATIVE IN THE EASTERN LITHUANIAN SUB-DIALECT OF UTENA: THE AUDITORY RESEARCH The results of auditory research on the shortened inessive and illative forms of the Eastern Lithuanian sub-dialect of Utena are discussed in this article. The phonemic structure of such forms coincides, eg. dirba laukuos : eina laukuos. The research aims to verify the existence of a prosodic element, i.e. the syllable accent of inessive and illative forms. During the auditory experiment, more than half of the researched pairs were correctly identified (65%); and the data of statistic evaluation (u criterion, 95% iterative interval) show that there is a high percentage of recognition, thereby showing few signs that the results are coincidental. Prior experiments and the auditory research carried out confirm the assumptions that the syllable accents in shortened inessive and illative forms are not homonymous in the Eastern Lithuanian sub-dialect of Utena. The realisation of accents is not always clearly heard; however the ability to discern different forms possessing the same phonemic structure should be treated as an indication that an opposition of syllable accents truly does exist.